DRIS Norms for Identifying Yield-Limiting Nutrients in Sapota (Manilkara achras (Mill). Fosberg) Cv. Cricketball - K Anjaneyulu (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2007)
Diagnosis and Recommendation Integrated System (DRIS) identified forty-five nutrient expressions as diagnostic norms from data colleted by surveying seventy-four sapota gardens in Karnataka and dividing the whole population into two sub-groups, namely, low and high yielding, during the year 2005-06. These expressions have shown higher variance and lower coefficient of variation found to have greater diagnostic precision, viz., N/K (0.989), Mg/N (0.264), N/Zn (0.117), Mg/K (0.258), Zn/K (8.609), S/Mg (0.666), Mg/Zn (0.031) etc. The Nutritional Balance Index indicated an overall imbalance of nutrients based on the sum of indices, irrespective of the sign. The diagnosis of nutrient imbalance through DRIS indices indicated that potassium, followed by nitrogen, was the most yieldlimiting nutrient among major nutrients and as were copper and zinc among micronutrients. In addition, five nutrient ranges were derived using mean and standard deviation as low, deficient, optimum, high and excess for each nutrient to serve as a guide for diagnostic purposes. Optimum N in the leaf ranged from 1.60 to 1.85%, P from 0.10 to 0.13%, K from 1.63 to 1.85%, Ca from 0.54 to 0.74%, Mg from 0.42 to 0.47% and S from 0.28 to 0.37%. Among micronutrients, optimum iron concentration in the leaf ranged from 113 to 161 ppm, Mn from 21-31 ppm, Zn from 14 to 17 ppm and Cu from 5 to 7 ppm for 'Criketball' variety of sapota.